Hemorrhagic Tamponade as Initial Manifestation of Systemic Lupus with Subsequent Refractory and Progressive Lupus Myocarditis Resulting in Cardiomyopathy and Mitral Regurgitation - Nicole Marijanovich; Alexandra Halalau (Case Reports in Rheumatology)
Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease with a wide range of clinical and serological manifestations. Cardiac disease among patients with SLE is common and can involve the pericardium, myocardium, valves, conduction system, and coronary arteries. We are reporting a case of SLE in a young woman that is unique is unique in that initial symptoms consisted of pericarditis and hemorrhagic tamponade which remained progressive and resistant to aggressive immunosuppressive treatment and led to severe cardiomyopathy (ejection fraction of 25%) and severe (+4) mitral regurgitation. Her immunosuppressive treatment included hydroxychloroquine, high-dose steroids, intravenous immunoglobulins, azathioprine, and mycophenolate mofetil. Her disease progression was felt to be due to underlying uncontrolled SLE because the complement levels remained persistently low throughout the entire course and PET Myocardial Perfusion and Viability study showed stable persistent active inflammation. Eventually, she was treated with cyclophosphamide which led to improvement in ejection fraction to 55% with only mild mitral regurgitation.